Penerapan Model PBL, Picture and Picture, dan Storytelling untuk Meningkatkan Keterampilan Berbicara pada Peserta Didik - Zira Shafira; Ramadi (Jurnal Pendidikan Sosial Dan Konseling, 2023)
The research problem is the low level of Indonesian speaking skills at SDN 3 Landasan Ulin Barat. This is due to the knowledge and experience of students in skills that are less visible in learning, because in Indonesian language the focus is on listening, reading, and writing. Affects the learning outcomes are not maximized in speaking skills. Therefore, it is necessary to make improvements using a combination of PBL, Picture and Picture, and Storytelling models. The purpose of this study is to describe the activities of educators and students' activities, and analyze the improvement of learning outcomes in speaking skills. This research uses Classroom Action Research (PTK) which applies a qualitative approach obtained from observations of educator activities, teacher activities, learning outcomes of speaking skills, while a quantitative approach for student learning outcomes obtained through written tests in groups and individually. The research was conducted as many as 4 meetings on grade 4 students of SDN 3 Landasan Ulin Barat, totaling 20 people. The data collection techniques used were observation, questionnaire and test. Indicators of success Student activity scores 22-38 with a classical ≥80% and individual learning outcomes of all students with ≥70 KKM with a classical ≥80%.